Ammonia gas sensor, preparation method thereof and ammonia gas detection device
By using polyaniline-bismuth oxychloride composite material to prepare ammonia sensors, the problems of low sensitivity and long recovery time of traditional ammonia sensors are solved, and efficient detection of low concentration ammonia is achieved.
Patent Information
- Application Number
- CN202411475511.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-17
AI Technical Summary
Traditional ammonia sensors have problems such as low sensitivity and long recovery time, and cannot effectively detect ammonia gases with a concentration of less than 1 ppm.
The polyaniline-bismuth oxychloride composite material is used as the gas-sensitive layer material to prepare an ammonia sensor through in-situ polymerization, which increases the diffusion channel and active site of ammonia, and improves the response intensity and recovery speed to ammonia.
The ammonia sensor has a strong response, fast recovery and high sensitivity, and can effectively detect ammonia gases below 0.5ppm.
Smart Images

Figure CN119322094A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of gas sensors, and in particular to an ammonia sensor and a preparation method thereof, and an ammonia detection device. Background Art
[0002] Ammonia is one of the common air pollutants, mainly from agriculture, animal husbandry and industrial production processes; ammonia is also a volatile gas produced during human metabolism and can be excreted from the body through the kidneys and liver. Therefore, manufacturing high-performance ammonia sensors is of great significance for environmental monitoring and human health protection.
[0003] When conductive polymers are exposed to oxidizing or reducing gas molecules at room temperature, the conductivity of the material changes, making them excellent sensitive materials for making room temperature gas sensors. Traditional gas-sensitive materials for ammonia detection usually include reduced graphene microspheres modified with sodium polystyrene sulfonate and polyaniline coated on the microspheres. However, they have problems such as small specific surface area and insufficient active sites, and low sensitivity to ammonia. The ammonia sensor finally prepared has shortcomings such as slow recovery and inability to detect gases with concentrations below 1ppm.
[0004] Therefore, it is necessary to improve the traditional ammonia sensor. Summary of the invention
[0005] Based on this, one or more embodiments of the present application provide an ammonia sensor with short recovery time and high sensitivity, a preparation method thereof, and an ammonia detection device.
[0006] According to a first aspect of an embodiment of the present application, there is provided an ammonia sensor, comprising a substrate, interdigital electrodes and a gas-sensitive layer;
[0007] The interdigital electrodes are arranged on at least one side of the substrate, and the gas-sensitive layer is arranged on a surface of the interdigital electrodes away from the substrate; the gas-sensitive layer comprises a polyaniline-bismuth oxychloride composite material, and the polyaniline-bismuth oxychloride composite material is prepared by in-situ polymerization.
[0008] In one embodiment, the polyaniline-bismuth oxychloride composite material is prepared by in-situ polymerization.
[0009] In one embodiment, the mass percentage of polyaniline in the polyaniline-bismuth oxychloride composite material is 80%-98%, and the mass percentage of bismuth oxychloride is 2%-20%.
[0010] In one embodiment, the ammonia sensor satisfies at least one of the following characteristics:
[0011] (1) The material of the substrate includes one or more of polyimide, polyethylene terephthalate, polyethylene naphthalate and polydimethylsiloxane;
[0012] (2) The number of the interdigital electrodes is 2 or more, and the distance between two adjacent interdigital electrodes is 1.8 mm to 2.2 mm.
[0013] In one embodiment, the steps include:
[0014] providing a dispersion comprising a polyaniline-bismuth oxychloride composite material;
[0015] The dispersion is applied onto the surface of the interdigital electrode away from the substrate, and dried to form a gas-sensitive layer, thereby preparing the ammonia sensor.
[0016] In one embodiment, the method for preparing the dispersion comprises the following steps:
[0017] Mixing bismuth oxide nanomaterials, hydrochloric acid solution and aniline to obtain a first solution;
[0018] The first solution is mixed with an ammonium persulfate / hydrochloric acid solution and then subjected to a polymerization reaction to prepare a polyaniline-bismuth oxychloride composite material;
[0019] The polyaniline-bismuth oxychloride composite material is mixed with a first solvent and subjected to ultrasonic treatment to obtain a dispersion.
[0020] In one embodiment, the preparation method satisfies at least one of the following characteristics:
[0021] (1) In the first solution, the ratio of the added amount of bismuth oxide nanomaterial to aniline is (1 mg~10 mg):0.1 mL;
[0022] (2) The concentration of the polyaniline-bismuth oxychloride composite material in the dispersion is 1 mg / L to 10 mg / L;
[0023] (3) the first solvent includes one or more of deionized water, N,N-dimethylformamide, N,N-dimethylacetamide, methanol, ethanol and acetone;
[0024] (4) The frequency of the ultrasonic treatment is 50kHz~100kHz, and the time is 10min~20min.
[0025] In one embodiment, the method for preparing the bismuth oxide nanomaterial comprises the following steps:
[0026] Stirring and mixing bismuth nitrate pentahydrate, trimesic acid and a second solvent to obtain a second solution;
[0027] subjecting the second solution to a hydrothermal reaction, washing, and drying to obtain a bismuth-based metal-organic framework;
[0028] The bismuth-based metal organic framework is sintered to obtain a bismuth oxide nanomaterial.
[0029] In one embodiment, the preparation method satisfies at least one of the following characteristics:
[0030] (1) The mass ratio of bismuth nitrate pentahydrate to trimesic acid in the second solution is 1:(2-7);
[0031] (2) the second solvent comprises N,N-dimethylformamide and methanol, and the volume ratio of N,N-dimethylformamide to methanol is (2-5):1;
[0032] (3) The stirring method is magnetic stirring or mechanical stirring;
[0033] (4) The stirring speed is 100 rpm~500 rpm, and the time is 10 min~30 min;
[0034] (5) The temperature of the hydrothermal reaction is 120℃~180℃, and the time is 12h~24h;
[0035] (6) The washing solvent includes one or more of N,N-dimethylformamide and methanol;
[0036] (7) The washing method is centrifugal washing, the centrifugal speed is 8000 rpm~10000 rpm, and the centrifugal time is 5 min~20 min;
[0037] (8) The sintering temperature is 500℃~600℃ and the time is 2h~4h.
[0038] According to a second aspect of an embodiment of the present application, an ammonia detection device is provided, comprising the above-mentioned ammonia sensor or an ammonia sensor prepared by the above-mentioned method for preparing the ammonia sensor.
[0039] Compared with the traditional technology, this application has the following beneficial effects:
[0040] The present application uses a polyaniline-bismuth oxychloride composite material as the gas-sensitive layer material of the ammonia sensor, so that the prepared ammonia sensor has the characteristics of strong response, fast recovery, high sensitivity, etc. Specifically, the strong covalent bond and weak van der Waals force of bismuth oxychloride can enhance its adsorption and residence time on ammonia molecules, while polyaniline has specific adsorption on ammonia, and the combination of the two can enhance the sensor's response to ammonia. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0042] Figure 1 This is a schematic diagram of the structure of an ammonia sensor in one embodiment of the present application;
[0043] Figure 2 This is a schematic diagram of the response principle of an ammonia sensor to ammonia according to one embodiment of the present application;
[0044] Figure 3 is a scanning electron microscope image of the polyaniline-bismuth oxychloride composite material in Example 1 of the present application;
[0045] Figure 4 This is a transmission electron microscope image of the polyaniline-bismuth oxychloride composite material in Example 1 of the present application;
[0046] Figure 5 This is a response curve of the ammonia sensor prepared in Example 1 of the present application to 100 ppm ammonia at room temperature;
[0047] Figure 6 This is a response curve diagram of the ammonia sensor prepared in Example 1 of the present application to ammonia of different concentrations.
[0048] The reference numerals in the drawings are: 10, substrate; 20, interdigital electrodes; 30, gas-sensitive layer. DETAILED DESCRIPTION
[0049] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0051] In the present application, "plurality", "multiple", "multiple times", "multiples", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0052] As used herein, "combination thereof", "any combination thereof", "any combination thereof" etc. include all suitable combinations of any two or more of the listed items.
[0053] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.
[0054] Herein, “preferred”, “better”, “more preferred” and “suitable” are merely used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute limitations on the scope of protection of this application.
[0055] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0056] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0057] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0058] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.
[0059] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0060] In a first aspect of the present application, an ammonia sensor is provided, comprising a substrate, interdigital electrodes and a gas-sensitive layer;
[0061] The interdigital electrodes are arranged on at least one side of the substrate, and the gas-sensitive layer is arranged on a surface of the interdigital electrodes away from the substrate; the gas-sensitive layer comprises a polyaniline-bismuth oxychloride composite material.
[0062] In some embodiments, the polyaniline-bismuth oxychloride composite material is prepared by in-situ polymerization.
[0063] In some embodiments, in the polyaniline-bismuth oxychloride composite material, polyaniline is interwoven to form dense fiber clusters; and bismuth oxychloride is distributed in the form of nanosheets between the polyaniline fiber clusters.
[0064] In some embodiments, the structure of the ammonia sensor is as follows Figure 1 shown.
[0065] When conductive polymers are exposed to oxidizing or reducing gas molecules at room temperature, the conductivity of the material changes, making them excellent sensitive materials for making room temperature gas sensors. Bismuth oxychloride is a layered structure composed of [X-Bi-O-Bi-X] sheets stacked along the c-axis through van der Waals interactions. Its strong covalent bonds and weak van der Waals interactions make bismuth oxychloride very attractive in many applications such as photocatalytic treatment of wastewater, indoor gas purification, and water purification. Polyaniline is an important conductive polymer with the advantages of easy availability of raw materials, simple synthesis process, and good environmental stability. It also has specific adsorption for ammonia and is an ideal material for building highly sensitive ammonia sensors.
[0066] Understandably, single bismuth oxychloride has the disadvantages of too large resistance and low sensitivity as a gas-sensitive material. By compounding polyaniline with bismuth oxychloride through in-situ polymerization, the carriers will shift due to the difference in Fermi level until the Fermi level reaches equilibrium, and a depletion layer will be formed on the interface during this process. The polyaniline between the bismuth oxychloride sheets increases the diffusion channel of ammonia and exposes more active sites on the surface of bismuth oxychloride. In addition, during the in-situ polymerization process, pp junctions appear between polyaniline nanofibers or between bismuth oxychloride and polyaniline, which plays an important role in improving gas-sensitive performance. Therefore, a safety sensor with strong response, short recovery time and high sensitivity can be prepared.
[0067] like Figure 2As shown, the ammonia sensor of the present application responds to ammonia by detecting the resistance change when polyaniline and bismuth oxychloride in the gas-sensitive layer interact with ammonia.
[0068] In some embodiments, the mass percentage of polyaniline in the polyaniline-bismuth oxychloride composite material is 80% to 98%, and the mass percentage of bismuth oxychloride is 2% to 20%.
[0069] As an example, the mass percentage of polyaniline can be but not limited to 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%; the mass percentage of bismuth oxychloride can be but not limited to 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0070] In some specific examples, the particle size of the polyaniline-bismuth oxychloride composite material is 150 nm to 300 nm.
[0071] In some embodiments, the material of the substrate includes one or more of polyimide, polyethylene terephthalate, polyethylene naphthalate and polydimethylsiloxane.
[0072] In some specific examples, the length of the substrate is 4 cm to 6 cm, the width is 1.5 cm to 2.5 cm, and the thickness is 0.15 mm to 0.25 mm.
[0073] In an optional example, the substrate has a length of 5 cm, a width of 2 cm, and a thickness of 0.2 mm.
[0074] In some embodiments, the number of the interdigital electrodes is more than 2, and the distance between two adjacent interdigital electrodes is 1.8 mm to 2.2 mm.
[0075] In an optional example, the distance between two adjacent interdigital electrodes is 2 mm.
[0076] In some specific examples, the thickness of the interdigital electrodes is 0.13 mm to 0.17 mm, and the width of the interdigital electrodes is 1.8 mm to 2.2 mm.
[0077] In an optional example, the thickness of the interdigital electrode is 0.15 mm, and the width of the interdigital electrode is 2 mm.
[0078] In some specific examples, the material of the interdigital electrodes includes copper foil.
[0079] In some specific examples, the thickness of the gas sensitive layer is 0.12 mm to 0.28 mm.
[0080] A second aspect of the present application provides a method for preparing the ammonia sensor of the first aspect, comprising step S100 and step S200.
[0081] Step S100: providing a dispersion liquid containing a polyaniline-bismuth oxychloride composite material;
[0082] Step S200: coating the dispersion onto the surface of the interdigital electrode away from the substrate, drying to form a gas sensitive layer, and preparing an ammonia sensor.
[0083] In some embodiments, in step S100, the step of providing a dispersion liquid containing a polyaniline-bismuth oxychloride composite material includes steps S110 to S130:
[0084] Step S110: uniformly mixing bismuth oxide nanomaterial, hydrochloric acid solution and aniline to obtain a first solution;
[0085] Step S120: mixing the first solution with the ammonium persulfate / hydrochloric acid solution and performing a polymerization reaction to prepare a polyaniline-bismuth oxychloride composite material;
[0086] Step S130: mixing the polyaniline-bismuth oxychloride composite material with the first solvent, and subjecting the mixture to ultrasonic treatment to obtain a dispersion.
[0087] In some specific examples, the bismuth oxide nanomaterial is a bismuth oxide nanorod with a diameter of 50 nm to 300 nm.
[0088] In some specific examples, in step S110, the ratio of the added amount of bismuth oxide nanomaterial to aniline in the first solution is (1 mg~10 mg):0.1 mL.
[0089] As an example, the ratio of the added amount of bismuth oxide nanomaterial to aniline can be but is not limited to 1 mg:0.1 mL, 2 mg:0.1 mL, 3 mg:0.1 mL, 4 mg:0.1 mL, 5 mg:0.1 mL, 6 mg:0.1 mL, 7 mg:0.1 mL, 8 mg:0.1 mL, 9 mg:0.1 mL or 10 mg:0.1 mL.
[0090] In some specific examples, step S110 includes the following steps: uniformly dispersing bismuth oxide nanomaterials in a hydrochloric acid solution, adding aniline at 0-4° C., and stirring uniformly to obtain a first solution.
[0091] In some specific examples, in step S110, the concentration of the hydrochloric acid solution is 1.8 mol / L to 2.2 mol / L; optionally 2 mol / L.
[0092] In some embodiments, the preparation of bismuth oxide nanomaterial in step S110 includes steps S111 to S113.
[0093] Step S111: mixing bismuth nitrate pentahydrate, trimesic acid and a second solvent, and stirring them uniformly to obtain a second solution;
[0094] Step S112: subjecting the second solution to a hydrothermal reaction, washing, and drying to obtain a bismuth-based metal organic framework;
[0095] Step S113: sintering the bismuth-based metal organic framework to obtain bismuth oxide nanomaterials.
[0096] In some specific examples, in step S111, the mass ratio of bismuth nitrate pentahydrate to trimesic acid in the second solution is 1:(2-7), and can be optionally 1:5.
[0097] In some specific examples, in step S111, the second solvent includes N,N-dimethylformamide and methanol, and the volume ratio of N,N-dimethylformamide to methanol is (2-5):1; optionally, 4:1.
[0098] In some specific examples, in step S111, the stirring method is magnetic stirring or mechanical stirring.
[0099] In some specific examples, in step S111, the stirring speed is 100 rpm to 500 rpm, and the time is 10 min to 30 min.
[0100] In some specific examples, in step S112, the temperature of the hydrothermal reaction is 120°C to 180°C, and the time is 12h to 24h; optionally, the temperature of the hydrothermal reaction is 120°C, and the reaction time is 24h.
[0101] In some specific examples, in step S112, the washing solvent includes one or more of N,N-dimethylformamide and methanol.
[0102] In some specific examples, in step S112, the washing method is centrifugal washing, the centrifugal speed is 8000rpm~10000rpm, and the centrifugal time is 5min~20min.
[0103] In some specific examples, in step S113, the sintering temperature is 500°C to 600°C, and the sintering time is 2h to 4h; 2h is optional.
[0104] In some specific examples, in step S113, the temperature is raised to the sintering temperature at a rate of 1°C / min to 5°C / min, and after sintering, the temperature is cooled to room temperature at a rate of 1°C / min to 20°C / min.
[0105] In some specific examples, in step S120, after the polymerization reaction, the steps of centrifugal washing and vacuum freeze drying of the product of the polymerization reaction are also included. Optionally, the product of the polymerization reaction is alternately washed with ethanol and deionized water; the total number of washings is 8 to 10 times. Optionally, the vacuum freeze drying time is 48 hours to 50 hours.
[0106] In some specific examples, in step S120, the polymerization reaction temperature is 0-4°C, and the reaction time is 11h-13h.
[0107] In some specific examples, in step S120, the concentration of the ammonium persulfate / hydrochloric acid solution is 0.08 mol / L to 0.12 mol / L; optionally 0.1 mol / L.
[0108] It should be noted that the "ammonium persulfate / hydrochloric acid solution" in the present application refers to a mixed solution of solid ammonium persulfate and hydrochloric acid, wherein the molar concentration of the hydrochloric acid solution is 2 mol / L; and the volume ratio of ammonium persulfate to hydrochloric acid is 2:1.
[0109] In some specific examples, in step S130, the concentration of the polyaniline-bismuth oxychloride composite material in the dispersion is 1 mg / L to 10 mg / L. As an example, the concentration of the polyaniline-bismuth oxychloride composite material in the dispersion can be, but is not limited to, specific values such as 1 mg / L, 2 mg / L, 3 mg / L, 4 mg / L, 5 mg / L, 6 mg / L, 7 mg / L, 8 mg / L, 9 mg / L or 10 mg / L.
[0110] In some specific examples, in step S130, the first solvent includes one or more of deionized water, N,N-dimethylformamide, N,N-dimethylacetamide, methanol, ethanol and acetone.
[0111] In some specific examples, in step S130, the frequency of the ultrasonic treatment is 50 kHz to 100 kHz, and the time is 10 min to 20 min. It can be understood that the polyaniline-bismuth oxychloride composite material can be uniformly dispersed in the first solvent by ultrasonic treatment, thereby obtaining a dispersion.
[0112] In a third aspect of the present application, an ammonia detection device is provided, comprising the ammonia sensor of the first aspect or the ammonia sensor prepared by the preparation method of the second aspect.
[0113] The ammonia detection device prepared using the above-mentioned ammonia sensor can be used to detect ammonia in the environment and ammonia exhaled by the human body, and has the advantages of strong response, fast recovery time, high sensitivity, etc.
[0114] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0115] Embodiment 1:
[0116] (1) Add 150 mg of bismuth nitrate pentahydrate and 750 mg of trimesic acid to 60 mL of a mixed solvent (a mixed solvent of N,N-dimethylformamide and methanol in a volume ratio of 4:1), stir at 800 rpm for 30 minutes, pour the solution into a 100 mL Teflon stainless steel autoclave, and keep it at 120°C for 24 hours for hydrothermal reaction. The white precipitate obtained by the reaction was washed five times with N,N-dimethylformamide and methanol respectively, and then dried in a vacuum at 60°C for 12 hours to obtain a bismuth-based metal organic framework (Bi-MOF).
[0117] (2) The temperature was raised to 500°C at a heating rate of 5°C / min and sintered for 2 hours, and then naturally cooled to room temperature to obtain Bi2O3 nanomaterials.
[0118] (3) Add 5 mg of the above Bi2O3 to 20 mL of 2 mol / L hydrochloric acid solution under ice bath conditions, stir at 500 rpm, and stir magnetically for 2 hours. Add 0.1 mL of aniline to the above solution and stir for 30 minutes to obtain a first solution.
[0119] 10 mL of 0.1 mol / L ammonium persulfate / hydrochloric acid solution was added dropwise to the first solution, and the polymerization reaction was carried out at 0°C to 4°C for 12 hours. After the reaction was completed, the sample was completely collected by suction filtration, and was washed alternately with ethanol and deionized water for 8 times to ensure that the reactants were completely removed. The product was vacuum freeze-dried for 48 hours to collect a polyaniline-bismuth oxychloride composite material.
[0120] (4) Adding polyaniline-bismuth oxychloride nanosheets into deionized water and subjecting the nanosheets to ultrasonic treatment at 40 kHz for 15 minutes, the composite material is evenly dispersed in the deionized water to obtain a dispersion containing the polyaniline-bismuth oxychloride composite material. The concentration of the polyaniline-bismuth oxychloride composite material in the dispersion is 1 mg / L.
[0121] (5) A flexible substrate was prepared using polyimide, and a copper foil was cut by laser into interdigitated electrodes with a thickness of 0.15 mm, an interdigitated width of 2 mm, and a gap distance of 2 mm between adjacent interdigitated electrodes, and the interdigitated electrodes were pasted on the flexible substrate. 5 μL of the dispersion containing the polyaniline-bismuth oxychloride composite material prepared in step (4) was added dropwise to the surface of the interdigitated electrodes, and vacuum dried at 60°C for 1 hour, thereby obtaining a polyaniline-bismuth oxychloride ammonia sensor.
[0122] Figure 3 This is a scanning electron microscope image of the polyaniline-bismuth oxychloride composite material prepared in this example. It can be seen that the bismuth oxychloride nanosheets are evenly and tightly compounded on the amorphous polyaniline.
[0123] Figure 4 This is a transmission electron microscope image of the polyaniline-bismuth oxychloride composite material prepared in this example, indicating that the bismuth oxychloride nanosheets are uniformly and tightly composited on the polyaniline.
[0124] Figure 5 This is a response curve of the polyaniline-bismuth oxychloride ammonia sensor prepared in this example to 100 ppm ammonia concentration at room temperature; the results show that the sensor prepared in this example has a strong response to nitrogen dioxide, with a response value of 325%, a response time of 11 seconds, and a recovery time of 39 seconds.
[0125] Figure 6 This is a response curve of the polyaniline-bismuth oxychloride ammonia sensor prepared in this example to different concentrations of ammonia. The results show that as the ammonia concentration increases, the response value of the gas sensor gradually increases, and the minimum detection concentration can reach 0.5ppm.
[0126] Embodiment 2:
[0127] The method is basically the same as Example 1, except that the sintering temperature in step (2) is different, specifically 600°C.
[0128] Embodiment 3:
[0129] It is basically the same as Example 1, except that the content of Bi2O3 added in step (3) is different, specifically 3 mg.
[0130] Embodiment 4:
[0131] Compared with Example 1, the difference is that bismuth oxychloride and polyaniline are simply mixed as the gas-sensitive coating material, and the specific steps are as follows:
[0132] (1) 0.005 mg of bismuth oxychloride and 0.005 mg of polyaniline were added to 10 mL of deionized water and ultrasonically treated at 40 kHz for 15 minutes to uniformly disperse the bismuth oxychloride and polyaniline in the deionized water, thereby obtaining a dispersion containing polyaniline and bismuth oxychloride.
[0133] (2) A flexible substrate was prepared using polyimide, and a copper foil was cut by laser into interdigitated electrodes with a thickness of 0.15 mm, an interdigitated width of 2 mm, and a gap distance of 2 mm between adjacent interdigitated electrodes, and the interdigitated electrodes were pasted on the flexible substrate. 5 μL of the dispersion prepared in step (1) was added dropwise to the surface of the interdigitated electrodes and dried under vacuum at 60°C for 1 hour, thereby obtaining a bismuth oxychloride-polyaniline ammonia sensor.
[0134] Comparative Example 1:
[0135] Compared with Example 1, the difference is that only polyaniline is used as the gas-sensitive coating material, and the specific steps are as follows:
[0136] (1) Preparation of a dispersion containing polyaniline: 0.1 mL of aniline was added to 20 mL of a 2 mol / L hydrochloric acid aqueous solution under ice bath conditions and stirred for 30 minutes to obtain a first solution. 10 mL of a 0.1 mol / L ammonium persulfate / hydrochloric acid solution was added dropwise to the first solution and the polymerization reaction was carried out at 0°C to 4°C for 12 hours. After the reaction was completed, the sample was completely collected by suction filtration and washed alternately with ethanol and deionized water for 8 times to ensure that the reactants were completely removed. The product was vacuum freeze-dried for 48 hours to obtain a polyaniline material. Polyaniline-bismuth oxychloride nanosheets were added to deionized water and ultrasonically treated at 40 kHz for 15 minutes to uniformly disperse the composite material in the deionized water, thereby obtaining a dispersion containing a polyaniline-bismuth oxychloride composite material, wherein the concentration of the polyaniline-bismuth oxychloride composite material in the dispersion was 1 mg / L.
[0137] (2) A flexible substrate was prepared using polyimide, and a copper foil was cut by laser into interdigitated electrodes with a thickness of 0.15 mm, an interdigitated width of 2 mm, and a gap distance of 2 mm between adjacent interdigitated electrodes, and the interdigitated electrodes were pasted on the flexible substrate. 5 μL of the dispersion prepared in step (1) was dropped onto the surface of the interdigitated electrodes and vacuum dried at 60°C for 1 hour to obtain a polyaniline ammonia sensor.
[0138] Comparative Example 2:
[0139] Compared with Example 1, the difference is that only bismuth oxychloride is used as the gas-sensitive coating material, and the specific steps are as follows:
[0140] (1) Preparation of a dispersion containing bismuth oxychloride: 150 mg of bismuth nitrate pentahydrate and 750 mg of trimesic acid were added to 60 mL of a mixed solvent (a mixed solvent of N,N-dimethylformamide and methanol in a volume ratio of 4:1), stirred at 800 rpm for 30 minutes, poured the solution into a 100 mL Teflon stainless steel autoclave, and kept at 120°C for 24 hours for hydrothermal reaction. The white precipitate obtained by the reaction was washed five times with N,N-dimethylformamide and methanol, and then dried in a vacuum at 60°C for 12 hours to obtain a bismuth-based metal organic framework (Bi-MOF). The temperature was raised to 500°C at a heating rate of 5°C / min and sintered for 2 hours, and then naturally cooled to room temperature to obtain Bi2O3 nanomaterials. Under ice bath conditions, 5 mg of the above Bi2O3 was added to 5 mL of 2 mol / L hydrochloric acid aqueous solution, stirred at a speed of 500 rpm, and magnetically stirred for 12 hours. After the reaction was completed, the sample was completely collected by suction filtration, and washed 8 times with ethanol and deionized water alternately to ensure that the reactants were completely removed. The product was vacuum freeze-dried for 48 hours to obtain bismuth oxychloride material.
[0141] (2) Adding polyaniline-bismuth oxychloride nanosheets into deionized water and subjecting the nanosheets to ultrasonic treatment at 40 kHz for 15 minutes, the composite material is evenly dispersed in the deionized water to obtain a dispersion containing the polyaniline-bismuth oxychloride composite material. The concentration of the polyaniline-bismuth oxychloride composite material in the dispersion is 1 mg / L.
[0142] (3) A flexible substrate was prepared using polyimide, and a copper foil was cut by laser into interdigitated electrodes with a thickness of 0.15 mm, an interdigitated width of 2 mm, and a gap distance of 2 mm between adjacent interdigitated electrodes, and the interdigitated electrodes were pasted on the flexible substrate. 5 μL of the dispersion prepared in step (1) was dropped onto the surface of the interdigitated electrodes and vacuum dried at 60°C for 1 hour, thereby obtaining a bismuth oxychloride ammonia sensor.
[0143] The ammonia sensors prepared by Examples 1 to 4 and Comparative Examples 1 to 2 were respectively used to detect 100 ppm ammonia at room temperature, and the response value, response time and recovery time are shown in Table 1; and each ammonia sensor was used to detect ammonia of different concentrations, and the minimum detection concentration is shown in Table 1.
[0144] Table 1
[0145]
[0146] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0147] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. An ammonia sensor, characterized in that: comprising a substrate, interdigitated electrodes and a gas-sensitive layer; The interdigital electrodes are arranged on at least one side of the substrate, and the gas-sensitive layer is arranged on a surface of the interdigital electrodes away from the substrate; the gas-sensitive layer comprises a polyaniline-bismuth oxychloride composite material, and the polyaniline-bismuth oxychloride composite material is prepared by in-situ polymerization.
2. The ammonia sensor according to claim 1, characterized in that: The polyaniline-bismuth oxychloride composite material is prepared by in-situ polymerization.
3. The ammonia sensor according to claim 1, characterized in that: The mass percentage of polyaniline in the polyaniline-bismuth oxychloride composite material is 80%-98%, and the mass percentage of bismuth oxychloride is 2%-20%.
4. The ammonia sensor according to any one of claims 1 to 3, characterized in that: The ammonia sensor meets at least one of the following characteristics: (1) The material of the substrate includes one or more of polyimide, polyethylene terephthalate, polyethylene naphthalate and polydimethylsiloxane; (2) The number of the interdigital electrodes is 2 or more, and the distance between two adjacent interdigital electrodes is 1.8 mm to 2.2 mm.
5. The method for preparing an ammonia sensor according to any one of claims 1 to 4, characterized in that: The steps include: providing a dispersion comprising a polyaniline-bismuth oxychloride composite material; The dispersion is applied onto the surface of the interdigital electrode away from the substrate, and dried to form a gas-sensitive layer, thereby preparing the ammonia sensor.
6. The method for preparing an ammonia sensor according to claim 5, characterized in that: The preparation method of the dispersion comprises the following steps: Mixing bismuth oxide nanomaterials, hydrochloric acid solution and aniline to obtain a first solution; The first solution is mixed with an ammonium persulfate / hydrochloric acid solution and then subjected to a polymerization reaction to prepare a polyaniline-bismuth oxychloride composite material; The polyaniline-bismuth oxychloride composite material is mixed with a first solvent and subjected to ultrasonic treatment to obtain a dispersion.
7. The method for preparing an ammonia sensor according to claim 6, characterized in that: The preparation method meets at least one of the following characteristics: (1) In the first solution, the ratio of the added amount of bismuth oxide nanomaterial to aniline is (1 mg~10 mg):0.1 mL; (2) The concentration of the polyaniline-bismuth oxychloride composite material in the dispersion is 1 mg / L to 10 mg / L; (3) the first solvent includes one or more of deionized water, N,N-dimethylformamide, N,N-dimethylacetamide, methanol, ethanol and acetone; (4) The frequency of the ultrasonic treatment is 50kHz~100kHz, and the time is 10min~20min.
8. The method for preparing an ammonia sensor according to any one of claims 6 to 7, characterized in that: The preparation method of the bismuth oxide nanomaterial comprises the following steps: Stirring and mixing bismuth nitrate pentahydrate, trimesic acid and a second solvent to obtain a second solution; subjecting the second solution to a hydrothermal reaction, washing, and drying to obtain a bismuth-based metal-organic framework; The bismuth-based metal organic framework is sintered to obtain a bismuth oxide nanomaterial.
9. The method for preparing an ammonia sensor according to claim 8, characterized in that: The preparation method meets at least one of the following characteristics: (1) The mass ratio of bismuth nitrate pentahydrate to trimesic acid in the second solution is 1:(2-7); (2) the second solvent comprises N,N-dimethylformamide and methanol, and the volume ratio of N,N-dimethylformamide to methanol is (2-5):1; (3) The stirring method is magnetic stirring or mechanical stirring; (4) The stirring speed is 100 rpm~500 rpm, and the time is 10 min~30 min; (5) The temperature of the hydrothermal reaction is 120℃~180℃, and the time is 12h~24h; (6) The washing solvent includes one or more of N,N-dimethylformamide and methanol; (7) The washing method is centrifugal washing, the centrifugal speed is 8000 rpm~10000 rpm, and the centrifugal time is 5 min~20 min; (8) The sintering temperature is 500℃~600℃ and the time is 2h~4h.
10. An ammonia detection device, characterized in that: An ammonia sensor comprising the ammonia sensor according to any one of claims 1 to 4 or an ammonia sensor prepared by the preparation method of the ammonia sensor according to any one of claims 5 to 9.
Citation Information
Cited By
Modified polyaniline flexible ammonia sensor and preparation method and application thereof
CN122836134A